Recurrent EWSR1-CREB3L1 Gene Fusions in Sclerosing Epithelioid Fibrosarcoma - Arbajian, Elsa; Puls, Florian; Magnusson, Linda; Thway, Khin; Fisher, Cyril; Sumathi, Vaiyapuri P.; Tayebwa, Johnbosco; Nord, Karolin H.; Kindblom, Lars-Gunnar; Mertens, Fredrik (The American journal of surgical pathology, 2014)
Sclerosing epithelioid fibrosarcoma (SEF) and lowgrade fibromyxoid sarcoma (LGFMS) are 2 distinct types of sarcoma, with a subset of cases showing overlapping morphologic and immunohistochemical features. LGFMS is characterized by expression of the MUC4 protein, and about 90% of cases display a distinctive FUS-CREB3L2 gene fusion. In addition, SEF is often MUC4 positive, but is genetically less well studied. Fluorescence in situ hybridization (FISH) studies have shown involvement of the FUS gene in the majority of so-called hybrid LGFMS/SEF and in 10% to 25% of sarcomas with pure SEF morphology. In this study, we investigated a series of 10 primary tumors showing pure SEF morphology, 4 cases of LGFMS that at local or distant relapse showed predominant SEF morphology, and 1 primary hybrid LGFMS/SEF. All but 1 case showed diffuse expression for MUC4. Using FISH, reverse transcription polymerase chain reaction, and/or mRNA sequencing in selected cases, we found recurrent EWSR1-CREB3L1 fusion transcripts by reverse transcription polymerase chain reaction in 3/10 pure SEF cases and splits and deletions of the EWSR1 and/or CREB3L1 genes by FISH in 6 additional cases. All 5 cases of LGFMS with progression to SEF morphology or hybrid features had FUS-CREB3L2 fusion transcripts. Our results indicate that EWSR1 and CREB3L1 rearrangements are predominant over FUS and CREB3L2 rearrangements in pure SEF, highlighting that SEF and LGFMS are different tumor types, with different impacts on patient outcome.
Keywords: Sclerosing epithelioid fibrosarcoma; Low-grade fibromyxoid sarcoma; Hybrid; Gene fusion; EWSR1; FUS; CREB3L; CREB3L